2022
DOI: 10.3389/fncel.2022.943506
|View full text |Cite
|
Sign up to set email alerts
|

Neuronal activity-dependent ATP enhances the pro-growth effect of repair Schwann cell extracellular vesicles by increasing their miRNA-21 loading

Abstract: Functional recovery after peripheral nerve injuries is critically dependent on axonal regeneration. Several autonomous and non-cell autonomous processes regulate axonal regeneration, including the activation of a growth-associated transcriptional program in neurons and the reprogramming of differentiated Schwann cells (dSCs) into repair SCs (rSCs), triggering the secretion of neurotrophic factors and the activation of an inflammatory response. Repair Schwann cells also release pro-regenerative extracellular ve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 56 publications
0
4
0
Order By: Relevance
“…[ 49 ] In animal models of nerve injury, SCs‐EVs have been confirmed to be effective in promoting regeneration. [ 13a,50 ] Nevertheless, EVs‐based therapies face a significant challenge due to the poor yield and low retention rate of EVs.…”
Section: Discussionmentioning
confidence: 99%
“…[ 49 ] In animal models of nerve injury, SCs‐EVs have been confirmed to be effective in promoting regeneration. [ 13a,50 ] Nevertheless, EVs‐based therapies face a significant challenge due to the poor yield and low retention rate of EVs.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have found that neuronal activity enhances the release of extracellular vesicles derived from SCs and transfers them to neurons. This effect is achieved by activating P2Y receptors on SCs after sensory neurons release activity‐dependent ATP (Saquel et al, 2022). The activation of purinergic receptors can lead to the calcium‐dependent release of ATP, UDP, growth factors, and cytokines in SCs, which activate neurons (Patritti‐Cram et al, 2021).…”
Section: Scs and The Generation Of Cancer Pain Mechanismsmentioning
confidence: 99%
“…Moreover, repair SCs (rSCs) could also release pro-regenerative EVs. Neuronal activity enhances the release of rSC-derived EVs and their transfer to neurons via the ATP-P2Y signaling pathway[ 87 ]. Mechanical stimuli could control the intercellular communication between neurons and SCs by changing the composition of miRNA in SC-EVs.…”
Section: Repair and Regeneration Effects Of Evsmentioning
confidence: 99%